Role of the Systemic Inflammatory Response Index in Predicting Disease Severity and Prognosis in Idiopathic Pulmonary Arterial Hypertension - Gao L; Zhang S; Zhao Z; Zhao Q; Yang T; Zeng Q; Zhang Y; Li X; Huang Z; Duan A; Luo Q; Liu Z (Dove Medical Press, 2024)
Luyang Gao,* Sicheng Zhang,* Zhihui Zhao, Qing Zhao, Tao Yang, Qixian Zeng, Yi Zhang, Xin Li, Zhihua Huang, Anqi Duan, Qin Luo, Zhihong Liu Center for Respiratory and Pulmonary Vascular Diseases, Fuwai Hospital, National Center for Cardiovascular Diseases, National Clinical Research Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhihong Liu; Qin Luo, Center for Respiratory and Pulmonary Vascular Diseases, Fuwai Hospital, National Center for Cardiovascular Diseases, National Clinical Research Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, No. 167 Beilishi Road, Xicheng District, Beijing, 100037, People's Republic of China, Tel/Fax +86-010-88396589, Email zhihongliufuwai@163.com; luoqin2009@163.comIntroduction: Mounting evidence indicates a possible connection between the systemic inflammatory response index (SIRI) and the prognosis of heart failure, but its role in idiopathic pulmonary arterial hypertension (IPAH) is not well understood. This study aimed to investigate the relationship between SIRI and variables such as functional ability, echocardiography results, hemodynamic measurements, and long-term outcomes in patients with IPAH.Methods: The study included 426 consecutive IPAH patients who underwent right heart catheterization at Fuwai Hospital from January 2013 to December 2020. SIRI was calculated using composite inflammation indicators from routine blood tests. The main outcome measure was clinical deterioration. Spearman correlation coefficients were used to assess associations between SIRI and indicators of IPAH severity. Receiver operating characteristic (ROC) curve analysis was conducted to determine the optimal SIRI threshold and predictive ability. Kaplan-Meier analysis and Cox proportional hazard models were used to examine the relationship between SIRI and clinical deterioration.Results: SIRI showed positive associations with indicators such as N-terminal pro-brain natriuretic peptide, right ventricular end-diastolic diameter, pericardial effusion, mean pulmonary arterial pressure, and pulmonary vascular resistance. Conversely, SIRI had inverse relationships with 6-minute walking distance and left ventricular end-diastolic diameter. Kaplan-Meier curves revealed a significantly higher rate of clinical deterioration in individuals with SIRI > 0.741 compared to those with SIRI ≤ 0.741 (P < 0.001). Adjusted Cox analysis showed SIRI remained an independent predictor of clinical worsening (hazard ratio 1.366, 95% confidence interval 1.073- 1.738, P = 0.011). ROC analysis demonstrated SIRI provided additional predictive value beyond the risk assessment score of the European Society of Cardiology/European Respiratory Society.Discussion: In summary, SIRI could predict the severity and prognosis of IPAH independently. It was associated with various indicators of IPAH severity and was a significant predictor of clinical deterioration. SIRI also offered additional predictive value beyond existing risk assessment scores.Keywords: prognosis, pulmonary arterial hypertension, risk factor, systemic inflammatory response index